Coated steel sheet and method for manufacturing the same
Patent Information
- Application Number
- CN202380036501.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-07
- Filing Date
- 2023-05-15
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-05-15
AI Technical Summary
虽然这是广泛使用的方法,但存在如下问题:一旦实施表面处理,之后就不能进行模具的调整
[0046]根据本发明,能够显著降低钢板与模具之间的摩擦系数。其结果,根据本发明,即使对于压制成型时容易产生裂纹的部位,也能够不产生裂纹地进行成型。另外,根据本发明,能够抑制面压高的部位的模具磨损。因此,本发明的被覆钢板具有极其良好的压制成型性,能够很好地适用于成型为复杂的形状。
Smart Images

Figure CN119156280B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to coated steel sheets, and more particularly to coated steel sheets with excellent press formability. Furthermore, this invention relates to a method for manufacturing the aforementioned coated steel sheets. Background Technology
[0002] Cold-rolled steel sheets, hot-rolled steel sheets, and other steel sheets are widely used in various fields. For example, in applications such as automobile bodies, steel sheets are generally pressed and formed. Therefore, steel sheets are required to have excellent pressability and formability.
[0003] In recent years, in particular, there has been a trend towards press molding to create more complex shapes in order to improve the appearance and design of products. Additionally, the integration of components to simplify manufacturing processes also reflects this trend towards press molding to create more complex shapes.
[0004] However, when pressing steel sheets into complex shapes, the sheets sometimes cannot withstand the forming process and break, or die galling occurs during continuous pressing. This, in turn, severely impacts the productivity of products such as automobiles. Therefore, there is a need to further improve press formability.
[0005] One method to improve compressibility is to surface-treat the mold used in compression molding. While this is a widely used method, it has the following drawbacks: once surface treatment is performed, mold adjustments are no longer possible. Additionally, it is costly.
[0006] One method to improve compressibility without surface treatment of the mold is to use high-viscosity lubricating oil. However, compressed parts obtained by this method are coated with high-viscosity lubricating oil, which sometimes leads to poor degreasing after compression molding, resulting in deterioration of paintability.
[0007] Therefore, instead of surface treatment and high-viscosity lubricating oil for molds, it is necessary to improve the compressibility of the steel sheet itself.
[0008] As a technique to improve the press formability of steel sheets, a surface treatment is proposed to form a lubricating film on the surface of the steel sheet.
[0009] For example, Patent Document 1 proposes a coated steel sheet with an acrylic resin coating formed on the surface of a galvanized steel sheet.
[0010] Patent document 2 proposes a method in which a solid lubricant protrudes 0.01 to 1.5 μm from the surface of a resin film formed on the surface of a metal plate.
[0011] Patent document 3 proposes to coat the surface of a metal product with a 0.5 to 5 μm film containing a lubricant in a polyurethane resin.
[0012] Patent document 4 proposes a coated steel sheet having an alkali-soluble organic coating in which a lubricant has been added to an epoxy resin.
[0013] Existing technical documents
[0014] Patent documents
[0015] Patent Document 1: Japanese Patent Application Publication No. 09-170059
[0016] Patent Document 2: Japanese Patent Application Publication No. 10-052881
[0017] Patent Document 3: Japanese Patent Application Publication No. 2000-309747
[0018] Patent Document 4: Japanese Patent Application Publication No. 2000-167981 Summary of the Invention
[0019] However, in the technologies proposed in Patent Documents 1-4, although a certain improvement in lubricity was observed due to the effect of the lubricant contained in the film, the formability in complex compression molding was not sufficient. Specifically, the following problems exist: cracks occur in crack-prone areas during compression molding, or mold wear occurs in areas where surface pressure is high.
[0020] The present invention was made in view of the above circumstances, and its object is to provide a coated steel sheet with excellent press-formability.
[0021] The inventors focused on coated steel sheets having a coating containing organic resin and wax, and conducted in-depth research to solve the above-mentioned problems, resulting in the following insights.
[0022] (1) If a steel sheet with a coating containing organic resin and wax is pressed, the coating is scraped off by the mold when sliding between the coating surface and the mold surface. The lubricating coating formed by the mixture of organic resin and wax in the coating then covers the sliding surfaces of the mold surface and the steel sheet. Therefore, in order to improve the press-forming properties, it is necessary to improve the sliding properties of the lubricating coating on the sliding surfaces of the mold surface and the steel sheet, that is, to reduce the coefficient of friction.
[0023] (2) By using specific organic resins and waxes, and by controlling the area ratio of the wax-deficient portion in the above-mentioned film and the average area of the wax-deficient portion, the coefficient of friction can be significantly reduced.
[0024] This invention is based on the above insights, and its main points are as follows.
[0025] 1. A coated steel plate comprising a base steel plate and a coating containing organic resin and wax disposed on at least one side of the base steel plate, wherein,
[0026] The aforementioned organic resin is selected from at least one of styrene-based resins, epoxy-based resins, phenolic resins, and polyester-based resins.
[0027] The aforementioned wax is a polyolefin wax with a melting point of 100℃~145℃ and an average particle size of less than 3.0μm.
[0028] In the aforementioned coating, the area ratio of the wax-deficient portion relative to the total area of the coating is 20.0% or less. The wax-deficient portion is defined as a region where the ratio of the mass of the wax to the mass of the organic resin is 1 / 10 or less.
[0029] The average area of the wax-deficient region is 50.0 μm. 2 the following,
[0030] The amount of film adhering to one side of the above-mentioned film is 0.3 g / m. 2 above.
[0031] 2. The coated steel sheet according to claim 1, wherein the proportion of the organic resin in the coating is 30% to 95% by mass.
[0032] The proportion of the wax in the above-mentioned coating is 5% to 50% by mass.
[0033] 3. The coated steel plate according to 1 or 2 above, wherein the arithmetic mean roughness Ra of the surface of the base steel plate is 0.4 μm to 2.5 μm.
[0034] 4. The coated steel sheet according to any one of claims 1 to 3 above, wherein the amount of film adhering to one side of the film is 2.5 g / m². 2 the following.
[0035] 5. The coated steel sheet according to any one of 1 to 4 above, wherein the organic resin is an alkali-soluble resin.
[0036] 6. The coated steel sheet according to any one of claims 1 to 5 above, wherein the coating further contains a rust inhibitor.
[0037] 7. The coated steel sheet according to claim 6 above, wherein the rust inhibitor is at least one selected from aluminum salts, zinc salts and zinc oxide of phosphates.
[0038] 8. The coated steel sheet according to any one of claims 1 to 7 above, wherein the coating further contains a dispersant.
[0039] 9. The coated steel sheet according to claim 8, wherein the dispersant is at least one selected from sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymers and sulfonic acid copolymers.
[0040] 10. The coated steel sheet according to any one of claims 1 to 9 above, wherein the coating further contains silicon dioxide.
[0041] 11. A method for manufacturing a coated steel sheet, comprising the method described in any one of 1 to 10 above, wherein a coating comprising an organic resin and a wax is applied to at least one side of a base steel sheet and dried, wherein...
[0042] The aforementioned organic resin is selected from at least one of styrene-based resins, epoxy-based resins, phenolic resins, and polyester-based resins.
[0043] The wax mentioned above is a polyolefin wax with a melting point of 100℃~145℃ and an average particle size of less than 3.0μm.
[0044] 12. The method for manufacturing the coated steel sheet according to 11 above, wherein the maximum temperature reached by the base steel sheet during drying is 60°C to the melting point of the wax.
[0045] 13. The method for manufacturing the coated steel sheet according to 11 or 12 above, wherein the proportion of the total solids content in the coating is 1% to 30% by mass.
[0046] According to the present invention, the coefficient of friction between the steel sheet and the mold can be significantly reduced. As a result, according to the present invention, even in areas prone to cracking during pressing, molding can be performed without cracking. Furthermore, according to the present invention, mold wear in areas with high surface pressure can be suppressed. Therefore, the coated steel sheet of the present invention has extremely good pressability and is well-suited for molding into complex shapes. Attached Figure Description
[0047] Figure 1 This is an example of a mapping image of the peak intensity ratio of wax components and organic resin components obtained by micro Raman spectroscopy.
[0048] Figure 2 This is an example of a mapping image of the peak intensity ratio of wax components and organic resin components obtained by micro Raman spectroscopy.
[0049] Figure 3 It represents analysis Figure 1 The distribution of wax-deficient areas is obtained by mapping the image.
[0050] Figure 4 It represents analysis Figure 2 The distribution of wax-deficient areas is obtained by mapping the image.
[0051] Figure 5 This is a simplified front view of the friction coefficient measuring device.
[0052] Figure 6 It means Figure 5 A simplified three-dimensional diagram of the flange shape and dimensions. Detailed Implementation
[0053] Hereinafter, examples of embodiments of the present invention will be described. It should be noted that, unless otherwise specified, in the following description, the unit "%" of content means "mass %".
[0054] (1) Covered steel plate
[0055] In one embodiment of the present invention, the coated steel plate includes a base steel plate and a coating disposed on at least one side of the base steel plate.
[0056] [Membrane]
[0057] The above-mentioned coating contains organic resin and wax. The components are described below.
[0058] (Organic resin)
[0059] In this invention, the organic resin acts as a binder to retain the wax on the surface of the steel plate. Inorganic binders, due to their low affinity for polyolefins, cannot achieve the effect of imparting lubricity by forming a lubricating film. Therefore, it is important that the aforementioned film contains an organic resin.
[0060] The organic resin described above is selected from at least one of styrene-based resins, epoxy resins, phenolic resins, and polyester resins. Alternatively, two or more resins may be mixed and used as the organic resin described above.
[0061] As the aforementioned styrene-based resin, any styrene-based resin can be used without particular limitation. Here, styrene-based resin refers to a polymer containing styrene monomers as constituent components, typically referring to homopolymers of styrene and copolymers containing styrene. Examples of such copolymers include copolymers of styrene with at least one selected from acrylic monomers, nitrile groups, ethylene, and butadiene. The aforementioned styrene-based resin is preferably a styrene-acrylic resin. By copolymerizing acrylic acid and styrene, the molding properties are further improved compared to the case without acrylic acid.
[0062] As the aforementioned epoxy resin, any epoxy resin may be used without particular limitation. Examples of such epoxy resins include bisphenol A type epoxy resin, bisphenol F type epoxy resin, and phenolic varnish type epoxy resin.
[0063] As the aforementioned phenolic resin, any phenolic resin can be used without particular limitation. As the aforementioned phenolic resin, a first-order phenolic resin that can be dissolved or dispersed in an aqueous solvent is preferred.
[0064] As the aforementioned polyester resin, any polyester resin can be used without particular limitation. As the aforementioned polyester resin, a polyester resin containing a monomer having a carboxyl group as a constituent component is preferred.
[0065] From the viewpoint of film removability, the aforementioned organic resin is preferably an alkali-soluble resin. That is, when steel sheets are used for automobile bodies, etc., and coating is applied after pressing and molding, if the organic resin is an alkali-soluble resin, the film can be removed (film removal) during the alkali degreasing process performed before coating. Therefore, subsequent coating can be performed smoothly.
[0066] The aforementioned coating can contain organic resin in any proportion. However, if the proportion of organic resin is too low, the influence of components other than organic resin becomes greater, and the effect of organic resin is relatively reduced. Therefore, from the viewpoint of improving the effect of organic resin, it is preferable that the proportion of organic resin in the aforementioned coating is 30% or more. By making the proportion of organic resin 30% or more, the effect of improving molding properties can be further improved, and the functions of organic resin such as release properties and adhesion can be fully utilized. The proportion of organic resin in the aforementioned coating is more preferably 40% or more, and even more preferably 50% or more. On the other hand, there is no particular upper limit to the proportion of organic resin, but in order to add a certain amount of wax as described below, it is preferable to be 95% or less, and more preferably 90% or less.
[0067] Here, the proportion of organic resin in the film is defined as the ratio of the mass of the solid component of the organic resin in the film to the total mass of the total solid component in the film.
[0068] The weight-average molecular weight of the aforementioned organic resin is not particularly limited. However, if the weight-average molecular weight is less than 5000, the rust prevention performance may be poor. Therefore, from the viewpoint of rust prevention, it is preferable that the weight-average molecular weight of the aforementioned organic resin is 5000 or more, more preferably 7000 or more, and even more preferably 9000 or more. On the other hand, if the weight-average molecular weight of the aforementioned organic resin exceeds 30000, the adhesion may deteriorate. Therefore, from the viewpoint of adhesion, it is preferable that the weight-average molecular weight of the aforementioned organic resin is 30000 or less, more preferably 25000 or less, and even more preferably 20000 or less.
[0069] Here, the mass-average molecular weight of the above-mentioned organic resin is determined based on JIS K 7252 "Plastics - Method for determining the average molecular weight and molecular weight distribution of polymers by size exclusion chromatography".
[0070] (wax)
[0071] Polyolefin wax is used as the wax described above. Polyolefin wax has low surface energy and self-lubricating properties. Therefore, excellent compressibility can be obtained by forming a film containing polyolefin wax on the surface of the base steel plate. Furthermore, the melting point of polyolefin can be relatively easily adjusted to the range described later by controlling its density and molecular weight. Among polyolefin waxes, polyethylene wax is preferred because it provides the best lubrication effect.
[0072] Melting point: 100~145℃
[0073] The melting point of the aforementioned polyolefin wax is 100℃ to 145℃. As mentioned above, polyolefin wax itself has self-lubricating properties. Furthermore, if the melting point of the polyolefin wax is within the above range, the polyolefin wax becomes semi-molten due to the frictional heat generated during compression molding and sliding with the mold. A lubricating film formed by the mixture of organic resin and wax coats the mold surface and the sliding surface of the steel plate. Consequently, direct contact between the mold and the steel plate is suppressed, thus significantly improving the compressibility.
[0074] If the melting point of the polyolefin wax is less than 100°C, it will completely melt due to the frictional heat generated during molding, thus failing to provide adequate lubrication and achieving the desired mold coating effect. Therefore, the melting point of the polyolefin wax is 100°C or higher, preferably 120°C or higher. On the other hand, if the melting point of the polyolefin wax is higher than 145°C, it will not melt due to the frictional heat during molding, resulting in insufficient lubrication and mold coating. Therefore, the melting point of the polyolefin wax is 145°C or lower, preferably 140°C or lower.
[0075] Here, the melting point of polyolefin wax is defined as the melting temperature determined based on JIS K 7121 "Method for determination of the transformation temperature of plastics".
[0076] Average particle size: below 3.0 μm
[0077] If the average particle size of the polyolefin wax is greater than 3.0 μm, the polyolefin wax tends to solidify in the coating, and the wax-deficient areas cannot meet the conditions described later. Furthermore, during compression molding, the organic resin and wax become difficult to mix when sliding with the mold, making it impossible to achieve the aforementioned coating effect and excellent compression molding properties. Therefore, the average particle size of the polyolefin wax is preferably 3.0 μm or less, more preferably 1.5 μm or less, more preferably 0.5 μm or less, and even more preferably 0.3 μm or less. On the other hand, there is no particular limitation on the lower limit of the average particle size of the polyolefin wax, but if it is too small, the polyolefin wax may sometimes dissolve in the lubricating oil during compression molding, reducing the lubricity improvement effect. Additionally, since the polyolefin wax tends to solidify in the coating, not only does the coating stability decrease, but large wax-deficient areas are also easily formed. Therefore, the average particle size of the polyolefin wax is preferably 0.01 μm or more, more preferably 0.03 μm or more.
[0078] Here, the aforementioned average particle size can be determined by observing the wax particles on the coating surface using a scanning electron microscope (SEM). That is, it is determined by acquiring an SEM image at a magnification corresponding to the particle size of the wax and performing image analysis. The average value of the equivalent circle diameter of each wax particle obtained through the above image analysis is taken as the aforementioned average particle size.
[0079] The following describes in detail the method for determining the average particle size of wax particles using SEM. When determining the average particle size of wax particles using SEM, it is necessary to sufficiently reduce the accelerating voltage in order to suppress electron beam diffusion and transmission and obtain information about wax particles near the film surface. Therefore, it is preferable to perform the measurement at an accelerating voltage of 1 kV or less. Furthermore, to prevent image obstruction caused by electrical charge during observation and to clearly identify wax particles, it is preferable to apply a coating of conductive materials such as C, Au, or Os. The film thickness of the aforementioned conductive material coating is preferably 2 nm or less. The measurement range of the SEM image must be able to identify wax particles and include a statistically significant number of wax particles. For example, when the diameter of the wax particles is 100 nm to 300 nm, it is preferable to have a pixel size of 30 nm or less and a measurement range of 10 μm × 10 μm or more. It should be noted that SEM images can be obtained by measuring multiple consecutive or arbitrary fields of view, and multiple SEM images can be obtained in a manner that satisfies the above-mentioned measurement range.
[0080] The aforementioned coating can contain wax in any proportion. However, if the proportion of wax in the coating is too high, the proportion of organic resin acting as a binder will be relatively reduced, and the wax component will easily detach. Furthermore, adhesion will decrease. Additionally, during the coating process, if the coating is not fully removed from the steel plate surface during the alkaline degreasing step, sufficient degreasing cannot be achieved, sometimes resulting in deteriorated coatability. Therefore, the proportion of wax in the aforementioned coating is preferably 50% or less, more preferably 30% or less.
[0081] On the other hand, there is no particular limitation on the lower limit of the aforementioned wax proportion. However, if the wax proportion is increased, there is a tendency for the area ratio and average area of the wax-deficient portion to decrease, as described later, and for the molding properties to improve. Therefore, from the viewpoint of further improving molding properties, it is preferable that the wax proportion in the aforementioned coating is 5% or more, and more preferably 10% or more.
[0082] Here, the proportion of wax in the coating is defined as the ratio of the mass of the solid component of the wax in the coating to the total mass of the total solid component in the coating.
[0083] (Wax-deficient area)
[0084] Area percentage of wax-deficient regions: below 20.0%
[0085] When a film containing organic resin and wax is formed on the surface of a base steel plate, the wax tends to solidify and distribute unevenly within the film. Consequently, areas with a significantly low proportion of wax (wax-deficient areas) are formed within the film. Furthermore, if the proportion of wax-deficient areas on the surface of the film is too high, the desired lubrication effect cannot be obtained in these wax-deficient areas during compression molding, resulting in a higher coefficient of friction. Therefore, the area ratio of wax-deficient areas relative to the entire film is preferably 20.0% or less, more preferably 15.0% or less, and even more preferably 10.0% or less. On the other hand, the lower the area ratio, the better the compression molding performance; therefore, the lower limit is not particularly limited and can be 0%.
[0086] Average area of wax-deficient regions: 50.0 μm 2 the following
[0087] As described above, reducing the area ratio of wax-deficient portions improves moldability. However, the researchers' findings indicate that even when the area ratio of wax-deficient portions is 20.0% or less, when the average area of the wax-deficient portions exceeds 50.0 μm... 2 At the same time, the desired compression molding properties cannot be obtained. The reasons are as follows.
[0088] That is, even if the total area ratio of wax-deficient portions is the same, the actual distribution of wax on the film surface is not necessarily the same. For example, sometimes many small-sized wax-deficient portions are dispersed on the film surface, and sometimes, as a result of wax solidification, although the number is small, there are large-sized wax-deficient portions on the film surface. Moreover, when the size of the wax-deficient portions is small, the adverse effect on lubrication is relatively slight, but if the size of the wax-deficient portions is larger than a certain level, it has a non-negligible effect on lubrication. Therefore, in this invention, the average area of the wax-deficient portions is set to 50.0 μm. 2 The preferred size is 20.0 μm. 2 Hereinafter, 10.0 μm is preferred.2 Below. On the other hand, the smaller the average area mentioned above, the better; therefore, there is no particular lower limit. However, from the point of view of industrial production, the average area of the wax-deficient portion mentioned above can be 2.0 μm. 2 The above can also be 5.0μm. 2 above.
[0089] Therefore, by controlling the distribution of wax in a manner that satisfies both the area ratio of wax-deficient portions and the average area of the aforementioned wax-deficient portions, the molding properties can be improved extremely effectively.
[0090] Here, a wax-deficient region is defined as a region in the coating where the mass ratio of wax to organic resin is 1 / 10 or less. Conversely, in regions outside the wax-deficient region of the coating, the mass ratio of wax to organic resin is greater than 1 / 10.
[0091] The average area and area ratio of the wax-deficient region can be determined using microspectrophotometry, which can measure the peaks attributed to the wax component and the organic resin component, respectively. Examples of such spectrophotometry include micro Raman spectroscopy and micro FT-IR spectroscopy. The specific method for determining the average area and area ratio of the wax-deficient region using spectrophotometry will be explained below.
[0092] First, a spectrophotometric method was used to obtain mapping images of the peak intensities corresponding to the wax component and the organic resin component, respectively. Then, by dividing the peak intensity of the wax component by the peak intensity of the organic resin component, a mapping image of the peak intensity ratio of the wax component to the organic resin component was obtained.
[0093] Next, the mapping image of the peak intensity ratio is converted into a mapping image of the mass ratio of wax component to organic resin component. This conversion from intensity ratio to mass ratio can be performed using a calibration curve. This calibration curve is pre-prepared by measuring the mapping of peak intensity ratios using multiple standard samples of films with known mass ratios of wax component to organic resin component.
[0094] Then, areas where the mass ratio of wax to organic resin is less than 1 / 10 are extracted as wax-deficient areas, and the area of each individual wax-deficient area is calculated using image analysis software. The average area of each individual wax-deficient area is calculated as the average area of the wax-deficient areas. In addition, the ratio of the total area of each individual wax-deficient area to the area of the measurement field of view is calculated as the area ratio of the wax-deficient areas.
[0095] When determining the area ratio and average area of the wax-deficient region, the peaks used for measurement can be the individual peaks attributed to the wax component and the organic resin component, respectively. However, to reduce noise, it is preferable to use peaks with the highest possible intensity. For example, in micro-Raman spectroscopy, the peak at 1295 cm⁻¹ corresponding to the bending vibration of CH₂ is preferred. -1 The peak is attributed to polyolefin waxes. Furthermore, it is preferable to use the 1000 cm⁻¹ peak corresponding to the stretching vibration of the aromatic ring chain. -1 The peaks are attributed to styrene-based resins, epoxy-based resins, phenolic resins, and polyester-based resins, which are organic resin components.
[0096] Furthermore, the measurement range of the peak intensity ratio mapping image must include the number of statistically significant wax-deficient regions, and is therefore preferably 80 μm × 80 μm or larger. It should be noted that the above measurement range can be a continuous field of view or a combination of multiple fields of view.
[0097] As described above, the upper limit of the average particle size of the wax in this invention is 3.0 μm. Therefore, from the viewpoint of determining the solidification state of the wax, it is preferable that the interval between each measurement point in the above-described mapping image is 3 μm or less, more preferably 2 μm or less.
[0098] Figure 1 , 2 This is an example of a mapping image of the peak intensity ratio of the wax component and the organic resin component obtained by micro Raman spectroscopy. The measurement range is 100 μm × 100 μm, and the measurement conditions are as described above. Figure 1 It is a mapping image of the peak intensity ratio of a relatively uniformly distributed wax film, while Figure 2 It is a mapping image of the peak intensity ratio of a wax film that is unevenly distributed (a wax condensation film).
[0099] Figure 3 , 4 This indicates separate analysis. Figure 1 , 2 The distribution of wax deficiency areas is obtained by mapping the peak intensity ratio as shown in the image. In the above analysis, firstly, a pre-prepared calibration curve is used to... Figure 1 , 2 The peak intensity ratio mapping image shown is transformed into a mass ratio mapping image. Then, image analysis software is used to display the wax deficiency areas in the mass ratio mapping image as white areas. The area ratio and average area of the wax deficiency areas are respectively... Figure 3 The content is 0.3% and 6.3μm. 2 ,exist Figure 4 The content was 33.6% and 112.1 μm. 2 .
[0100] Rust Inhibitor
[0101] The aforementioned coating will not rust under normal storage conditions, even without the presence of a rust inhibitor. However, from the viewpoint of further improving rust resistance, the aforementioned coating preferably contains a rust inhibitor.
[0102] As the aforementioned rust inhibitor, any rust inhibitor can be used without particular limitation, but at least one selected from aluminum salts, zinc salts, and zinc oxide of phosphates is preferred. Here, phosphates include not only orthophosphoric acid but also condensed phosphoric acid such as pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid, and metaphosphoric acid. Using these rust inhibitors can achieve superior rust prevention, resulting in less deterioration of coating stability.
[0103] There is no particular limitation on the content of rust inhibitor, but if the content is too low, sufficient effectiveness may not be achieved. This is especially true when the coated steel sheet is stored in an overlapping coil state, where it is prone to rusting due to moisture absorption. From the viewpoint of preventing rust even in such harsh environments, it is preferable to have a rust inhibitor content of 5% or more in the coating. On the other hand, if the rust inhibitor content in the coating exceeds 30%, adhesion may deteriorate. Furthermore, in the coated state, rust inhibitor may sometimes precipitate, deteriorating the coating's stability. Therefore, it is preferable to have a rust inhibitor content of 30% or less in the coating.
[0104] Here, the proportion of rust inhibitor in the coating is defined as the ratio of the mass of rust inhibitor in the coating to the total mass of the total solid components in the coating.
[0105] [Dispersant]
[0106] From the viewpoint of improving the dispersibility of the coating components, the aforementioned coating preferably further contains a dispersant. As the dispersant, any dispersant can be used without particular limitation, but anionic polymeric dispersants are preferred. Anionic polymeric dispersants are particularly effective in improving the dispersibility of particles smaller than a few μm and can also adsorb onto polyolefin waxes. As the aforementioned anionic polymeric dispersant, at least one selected from sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymers, and sulfonic acid copolymers is preferred.
[0107] The proportion of dispersant in the film is not particularly limited, but is preferably 0.5% or more. If the proportion of dispersant in the film is 0.5% or more, the dispersibility of wax in the coating is improved, and the uniformity of wax distribution in the resulting film is improved. As a result, the desired wax distribution is easily achieved, and the molding properties are further improved. On the other hand, if the proportion of dispersant in the film exceeds 5%, adhesion may sometimes deteriorate. Therefore, the proportion of dispersant in the film is preferably 5% or less.
[0108] Here, the proportion of dispersant in the film refers to the ratio of the mass of the dispersant in the film to the total mass of the solid components of all components in the film.
[0109] (Silicon dioxide)
[0110] From the viewpoint of improving the waterproof and rust-proof properties of the coating, it is preferable that the above-mentioned coating further contains silica. Furthermore, by containing silica, the precipitation of rust inhibitors contained in the coating can be inhibited, thereby improving the stability of the coating.
[0111] Any type of silica can be used without particular limitation as the aforementioned silica. Colloidal silica is preferred. The average particle size of the colloidal silica is not particularly limited, but is preferably 5 nm or more. Furthermore, the average particle size of the colloidal silica is preferably 200 nm or less. The average particle size of the colloidal silica can be determined by dynamic light scattering. Specifically, firstly, the particle size distribution under a scattering intensity reference is determined by dynamic light scattering. Next, the particle size distribution is converted from the scattering intensity reference to a volume reference. The median particle size D50 in the obtained volume reference particle size distribution is taken as the average particle size of the colloidal silica.
[0112] The proportion of silica in the aforementioned coating is preferably 1% or more. By ensuring that the proportion of silica in the coating is 1% or more, the waterproofness and rust resistance of the coating are improved. On the other hand, if the proportion of silica in the coating exceeds 10%, the adhesion may sometimes deteriorate. Therefore, the proportion of silica in the aforementioned coating is preferably 10% or less.
[0113] Here, the proportion of silica in the coating refers to the ratio of the mass of silica in the coating to the total mass of the solid components of all components in the coating.
[0114] It should be noted that the proportions of the components contained in the above-mentioned coating can be calculated based on the mass of the solid components of each coating component during coating mixing.
[0115] In addition to the aforementioned organic resins, waxes, rust inhibitors, dispersants, and silica, the coating may contain any other ingredients. Examples of such other ingredients include surface conditioners and defoamers commonly added to coatings.
[0116] Adhesion amount: 0.3g / m 2 above
[0117] When the amount of the above-mentioned film attached is less than 0.3 g / m 2During the coating process, wax solidification easily occurs between coating application and drying, preventing the desired wax distribution and resulting in reduced moldability. Therefore, the adhesion amount on one side of the coating is 0.3 g / m². 2 The above should be noted. As will be explained later, the final wax distribution is affected by the surface roughness of the substrate steel plate. Therefore, from the viewpoint that the desired wax distribution can be easily obtained even when the surface roughness of the substrate steel plate is large, it is preferable to have an adhesion amount of 0.4 g / m² on one side of the coating. 2 The above, more preferably 0.6 g / m 2 The above is further preferred to be 0.8 g / m 2 That's all. On the other hand, there is no particular upper limit to the amount of film adhering to the coating, but if it exceeds 2.5 g / m... 2 If this happens, weldability, release properties, and adhesion may deteriorate. Therefore, the preferred adhesion amount on one side of the coating is 2.5 g / m². 2 the following.
[0118] The amount of film adhering can be determined by removing the film from the coated steel plate and dividing the mass difference before and after film removal by the area of the steel plate. The film can be removed by any method that removes only the film without damaging the base steel plate. Typically, solvents capable of dissolving the organic resin constituting the film (organic solvents, etc.), or stripping agents containing the aforementioned solvents, can be used. When the film is alkali-soluble, an alkali degreasing agent is preferred, as described in the examples.
[0119] [Base steel plate]
[0120] As described above, in this invention, excellent compressibility is achieved by controlling the composition of the coating and the distribution of wax within the coating. Therefore, any steel sheet can be used as the base steel sheet without particular limitation. The base steel sheet can be a cold-rolled steel sheet or a hot-rolled steel sheet.
[0121] The tensile strength TS of the aforementioned base steel plate is not particularly limited, but if it is too low, the strength of the final pressed part may be insufficient. Therefore, the tensile strength of the aforementioned base steel plate is preferably 260 MPa or higher. On the other hand, there is no particular limitation on the upper limit of the aforementioned tensile strength. For example, when a high-strength steel plate with a tensile strength of 440 MPa or higher is used as the base steel plate, the surface pressure during pressing becomes high. However, according to the present invention, the coefficient of friction between the steel plate and the die can be significantly reduced, so even under such high surface pressure conditions, the generation of cracks and die wear can be suppressed, and good pressability can be obtained. Therefore, the tensile strength of the base steel plate can be 440 MPa or higher. However, if the tensile strength is too high, it is difficult to press into complex shapes. Therefore, from the viewpoint of pressability to complex shapes, the tensile strength of the aforementioned base steel plate is preferably 440 MPa or lower.
[0122] The thickness of the base steel plate is not particularly limited, but if it is too thin, the strength of the resulting pressed part may be insufficient. Therefore, the thickness of the base steel plate is preferably 0.5 mm or more. On the other hand, there is no particular upper limit to the thickness, but if it is too thick, it is difficult to press it into complex shapes. Therefore, the thickness of the base steel plate is preferably 4.0 mm or less.
[0123] The surface roughness of the base steel plate (the surface roughness of the base steel plate before film formation) is not particularly limited. However, when the arithmetic mean roughness Ra of the base steel plate surface is greater than 2.5 μm, the surface of the base steel plate is uneven, making it difficult for the film formed in the concave areas to contact the mold during pressing. Furthermore, in the convex areas, the amount of film adhering is less compared to the concave areas, making it difficult to obtain the desired wax distribution, and sometimes reducing the improvement in pressability. Therefore, from the viewpoint of further improving pressability, it is preferable to have Ra of 2.5 μm or less. On the other hand, when Ra is less than 0.4 μm, micro-scratches that may occur during pressing are easily noticeable. Additionally, if Ra is less than 0.4 μm, wear may sometimes occur during pressing. Therefore, Ra is preferably 0.4 μm or more.
[0124] Here, the arithmetic mean roughness Ra of the base steel plate can be measured according to JIS B 0633:2001 (ISO 4288:1996). For example, when Ra is greater than 0.1 and less than 2, the cutoff value and reference length are set to 0.8 mm, the evaluation length is set to 4 mm, and Ra is calculated based on the measured roughness curve. When Ra is greater than 2 and less than 10, the cutoff value and reference length are set to 2.5 mm, the evaluation length is set to 12.5 mm, and Ra is calculated based on the measured roughness curve.
[0125] (2) Manufacturing method
[0126] Next, the method for manufacturing the coated steel sheet of the present invention will be described. In one embodiment of the present invention, the coated steel sheet is manufactured by applying a coating comprising organic resin and wax to at least one side of a base steel sheet and drying it. It should be noted that, unless otherwise specifically mentioned, the same principle applies as in the description of the coated steel sheet above.
[0127] As the aforementioned coating, for example, a coating made by adding wax to an organic resin solution in which the organic resin is dissolved in a solvent, or an organic resin emulsion in which the organic resin is dispersed in a solvent, can be used. As the aforementioned solvent, one or both of water and an organic solvent can be used, but water is preferred.
[0128] There is no particular limitation on the proportion of total solids in the coating, but it is preferably 1% to 30%. When the proportion of total solids in the coating is less than 1% or more than 30%, uneven coating may occur, and the desired wax distribution may not be obtained. It should be noted that the proportion of total solids in the coating here refers to the concentration of total solids in the coating, that is, the proportion of the mass of solids to the total mass of the coating (including solvents).
[0129] The coating of the substrate steel plate can be performed by any method without particular limitation. Examples of such coating methods include using a roller coater, a bar coater, or coating methods such as spraying, dipping, or brushing. In the above coating processes, the film adhesion amount on one side of the final coated steel plate is 0.3 g / m² based on dry weight. 2 Apply the coating using the methods described above.
[0130] Drying after coating can be carried out by any method without particular limitation. Examples of such drying methods include drying with hot air, drying with an IH heater, and drying with infrared heating.
[0131] The maximum temperature reached during drying of the steel plate is preferably 60°C to the melting point of the wax used. If the maximum temperature is less than 60°C, drying will take longer and sometimes the rust prevention will be poor. On the other hand, when the maximum temperature exceeds the melting point of the wax, the wax melts and clumps together, resulting in coarser particle sizes, making it difficult to obtain the desired wax distribution.
[0132] Example
[0133] The present invention will now be described through examples. It should be noted that the present invention is not limited to the examples described below.
[0134] To manufacture a coated steel sheet, a coating is formed on the surface of a base steel sheet by following these steps.
[0135] First, four types of base steel plates with the arithmetic mean roughness Ra shown in Table 1 were prepared. Base steel plates A through C were cold-rolled steel plates with a thickness of 0.8 mm, and base steel plate D was a hot-rolled steel plate with a thickness of 2.0 mm. It should be noted that base steel plates A through D are both SPCD (JIS G 3141) and SPHD (JIS G 3131) with a tensile strength of 270 MPa.
[0136] Furthermore, coatings with the compositions shown in Tables 2 and 3 were prepared. The proportions of each component in Tables 2 and 3 are the ratios of the mass of the solid component of each component in the coating to the total mass of the total solid component. It should be noted that colloidal silica with a volume average particle size of 9 nm was used as silica. In addition, the molecular weights of the organic resins and the melting points and average particle sizes of the waxes shown in Tables 2 and 3 are values determined by the methods described above.
[0137] The aforementioned coating was applied to the surface of the base steel plate using a bar coater. The plate was then heated and dried using an IH heater to achieve a maximum surface temperature of 80°C, resulting in a coated steel plate. The combinations of base steel plates and coatings used are shown in Tables 4-7. It should be noted that, for comparison purposes, in some comparative examples, film formation was not performed, and the base steel plates were directly provided for the evaluation described later.
[0138] (Coating adhesion amount)
[0139] The amount of film adhering to the coated steel sheet was determined. Specifically, the film was removed from the coated steel sheet, and the mass difference before and after film removal was divided by the area of the steel sheet to determine the amount of film adhering. The film was removed by immersing the coated steel sheet in a degreasing solution with a degreasing agent concentration of 20 g / L and a temperature of 40°C for 300 seconds. As the degreasing agent, FINE CLEANER E6403 (manufactured by Nihon Parkerizing Co., Ltd.) was used as an alkaline degreasing agent. It should be noted that the complete removal of the film under the above conditions was confirmed by the same method as the film removal test described later. The film adhering amounts shown in Tables 4 to 7 are values for one side of the steel sheet.
[0140] (Wax-deficient area)
[0141] Next, the area ratio and average area of the wax-deficient portion on the surface of the coated steel plate are evaluated according to the following steps.
[0142] First, five 10mm × 10mm test pieces were cut from each of the aforementioned coated steel plates. Using a micro Raman spectroscopy system (LabRAM HR Evolution, manufactured by Horiba Ltd.), the peak intensities near the center of each test piece were measured, obtaining mapping images corresponding to the wax and organic resin components, respectively. The measurement range was 100μm × 100μm, with a measurement interval of 1μm. Additionally, a 1295cm² microscope was used. -1 The peak, representing the wax component, was measured using a 1000 cm⁻¹. -1 The peak is the peak of the organic resin component.
[0143] Next, a mapping image of the peak intensity ratio of the wax component to the organic resin component is created by dividing the peak intensity of the wax component in the obtained mapping image by the peak intensity of the organic resin component. Then, using a pre-made calibration curve, the mapping image of the peak intensity ratio is converted into a mapping image of the mass ratio of the wax component to the organic resin component.
[0144] In the obtained mass ratio mapping image, measurement points where the mass ratio of wax to organic resin is 1 / 10 or less were identified as wax-deficient areas, and the area ratio and average area of these wax-deficient areas were calculated. However, the area was 4 μm. 2 The wax-deficient areas described below are not treated as wax-deficient areas and are excluded from the calculation of the area ratio and average area mentioned above.
[0145] The above measurements were performed on five test pieces, and the obtained area ratio and average area, along with their respective average values, were used as the area ratio and average area of the wax-deficient region. The results are shown in Tables 4-7.
[0146] Next, the properties of the obtained coated steel sheet will be evaluated according to the following steps.
[0147] (Compression molding properties)
[0148] Formability is related to slip properties, i.e., the coefficient of friction of the steel sheet surface; the lower the coefficient of friction, the better the formability. Therefore, to evaluate formability, the coefficient of friction of the resulting coated steel sheet is determined according to the following steps.
[0149] Figure 5This is a simplified front view of the friction coefficient measuring device. As shown in the figure, a friction coefficient measuring sample 1, taken from a coated steel plate, is fixed to a sample stage 2, which is fixed to the upper surface of a horizontally movable sliding stage 3. A sliding stage support 5, with a roller 4 in contact with it and capable of vertical movement, is provided on the lower surface of the sliding stage 3. A first weighing sensor 7 is mounted on the sliding stage support 5, and is used to measure the pushing load N generated by the flange 6 on the friction coefficient measuring sample 1 by pushing the sliding stage support 5 upward. A second weighing sensor 8 is mounted at one end of the sliding stage 3, and is used to measure the sliding resistance F that causes the sliding stage 3 to move horizontally under the aforementioned pushing force. It should be noted that PRETON R352L, a pressing cleaning oil manufactured by SUGIMURA Chemical Industrial Co., Ltd., is used as a lubricant applied to the surface of the sample 1 for testing.
[0150] Figure 6 This is a simplified perspective view showing the shape and dimensions of the flange used. The lower surface of flange 6 slides while being pressed against the surface of sample 1. Figure 6 The flange 6 shown has a width of 10 mm, a sliding length of 59 mm, and the lower part at both ends of the sliding direction is composed of a curved surface with a curvature of 4.5 mmR. The lower surface of the flange that pushes the sample has a plane with a width of 10 mm and a sliding length of 50 mm.
[0151] Friction coefficient determination test used Figure 6 The flange shown is subjected to a pressing load N of 400 kgf and a traction speed of the specimen (horizontal movement speed of the sliding table 3) of 20 cm / min. The coefficient of friction μ between the specimen and the flange is calculated by the formula: μ = F / N.
[0152] The obtained friction coefficient values are shown in Tables 4-7. When the friction coefficient is below 0.115, it is judged to have good pressing and forming properties (sliding properties).
[0153] (Weldability)
[0154] When press-formed parts obtained by pressing coated steel sheets are used in automobile bodies, welding is usually performed during the assembly process. Therefore, in addition to press-formability, excellent weldability is desired for the coated steel sheets. Thus, the weldability of the coated steel sheets is evaluated. Specifically, a continuous spot welding test is conducted on the coated steel sheets under the following conditions: electrode: DR type Cr-Cu electrode; pressure: 150 kgf; energizing time: 10 cycles / 60 Hz; welding current: 7.5 kA. The number of consecutive spots is determined. When the number of consecutive spots is 5000 or more, the weldability is evaluated as "good"; when it is less than 5000 spots, the weldability is evaluated as "insufficient".
[0155] (Shedding property)
[0156] Assuming the coated steel sheet of the present invention is used in an automotive application, the degreasing performance during degreasing is evaluated. To determine the degreasing performance, each coated steel sheet was first immersed in a degreasing solution with a degreasing agent concentration of 20 g / L and a temperature of 40°C for a specified time, followed by rinsing with tap water to perform degreasing. As the degreasing agent, FINECLEANER E6403 (manufactured by Nihon Parkerizing Co., Ltd.), an alkaline degreasing agent, was used.
[0157] Next, the surface carbon strength of the degreased test piece was measured using a fluorescence X-ray analysis device. Using the measured surface carbon strength, along with the pre-measured surface carbon strength before degreasing and the surface carbon strength of the substrate steel plate, the film peeling rate was calculated using the following formula.
[0158] Coating peel rate (%) = [(Surface carbon strength before degreasing - Surface carbon strength after degreasing) / (Surface carbon strength before degreasing - Surface carbon strength of the base steel plate)] × 100
[0159] It should be noted that, here, the surface carbon strength of the base steel plate refers to the surface carbon strength of the base steel plate before the coating is formed.
[0160] The above tests were conducted by varying the immersion time in the degreasing solution to determine the immersion time in the alkaline degreasing solution that resulted in a film peeling rate of 98% or higher. The determined immersion time is shown as the "film removal time" in Tables 4-7. When the above film removal time is less than 120 seconds, it is considered to have good film removal properties.
[0161] (Rust prevention)
[0162] Assuming the coated steel sheet is stored in a coiled state, the rust resistance under the overlapping state is evaluated. Specifically, a test piece measuring 150mm × 70mm is taken from the coated steel sheet, and rust resistance is assessed by applying 1.0g / m² of resin to each side of the test piece. 2 The adhesion amount was determined by applying rust-preventive oil to both sides. Next, two test pieces were overlapped and subjected to a surface pressure of 0.02 kgf / mm². 2 Under applied load, it is maintained in an environment with a temperature of 50°C and a humidity of 95%RH.
[0163] Every 7 days, check the overlapping inner surfaces and evaluate the number of days until rust appears. Cases with more than 56 days until rust appears are rated as "Excellent", cases with more than 21 days are rated as "Good", and cases with less than 21 days are rated as "Acceptable".
[0164] (Adhesion)
[0165] When press-formed parts obtained by pressing coated steel sheets are used in automobile bodies, bonding is sometimes performed during the assembly process. Therefore, it is desirable for the coated steel sheets to have excellent adhesion in addition to press-formability. Therefore, the adhesion of the coated steel sheets was evaluated. Specifically, two test pieces of 100×25.4mm each were taken from each coated steel sheet and immersed in rust-preventive oil. After the test pieces were pulled out of the rust-preventive oil, they were held vertically for 24 hours to remove excess oil.
[0166] Next, an epoxy adhesive with a uniform thickness of 0.2 mm was applied to a 25.4 mm × 13 mm area on the surface of the test piece. Then, the two test pieces were clamped together and baked at 180°C for 20 minutes for drying and curing. After cooling, a shear tensile test was performed using an Autograph testing machine to determine the shear bond strength. A shear bond strength of 20 MPa or higher was considered good adhesion.
[0167] As shown in Tables 4-7, the coated steel sheets that meet the conditions of this invention all have a friction coefficient of less than 0.115, exhibiting excellent press-formability. In contrast, the coated steel sheets that do not meet the conditions of this invention all have a friction coefficient higher than 0.115, resulting in poor press-formability.
[0168] As described above, the coated steel sheet of the present invention has excellent sliding properties (press forming properties) during pressing and forming, and is suitable for various applications, such as automobile body applications.
[0169] Table 1
[0170] A 0.48 B 0.78 C 1.48 D 2.35
[0171]
[0172]
[0173]
[0174]
[0175]
[0176]
[0177] Symbol Explanation
[0178] 1. Sample for determining the coefficient of friction
[0179] 2. Sample stage
[0180] 3 Sliding platform
[0181] 4 rollers
[0182] 5. Sliding table support platform
[0183] 6 flanges
[0184] 7 First Weighing Sensor
[0185] 8 Second Weighing Sensor
[0186] 9 guide rails
Claims
1. A coated steel plate comprising a base steel plate and a coating containing an organic resin and a wax disposed on at least one side of the base steel plate, wherein, The arithmetic mean roughness Ra of the base steel plate surface is 0.4 μm to 2.5 μm. The organic resin is selected from at least one of styrene-based resins, epoxy-based resins, phenolic resins, and polyester-based resins. The wax is a polyolefin wax with a melting point of 100℃~145℃ and an average particle size of less than 3.0μm. In the coating, the area ratio of the wax-deficient portion relative to the total area of the coating is 20.0% or less. The wax-deficient portion is defined as a region where the ratio of the mass of the wax to the mass of the organic resin is 1 / 10 or less. The average area of the wax-deficient region is 50.0 μm. 2 the following, The amount of film adhering to one side is 0.3 g / m. 2 above.
2. The coated steel plate according to claim 1, wherein, The proportion of the organic resin in the coating is 30% to 95% by mass. The proportion of wax in the coating is 5% to 50% by mass.
3. The coated steel plate according to claim 1 or 2, wherein, The amount of film adhering to one side is 2.5 g / m. 2 the following.
4. The coated steel plate according to claim 1 or 2, wherein, The organic resin is an alkali-soluble resin.
5. The coated steel plate according to claim 1 or 2, wherein, The coating further contains a rust inhibitor.
6. The coated steel plate according to claim 5, wherein, The rust inhibitor is at least one selected from aluminum salts, zinc salts, and zinc oxide of phosphates.
7. The coated steel plate according to claim 1 or 2, wherein, The film further contains a dispersant.
8. The coated steel plate according to claim 7, wherein, The dispersant is at least one selected from sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymers, and sulfonic acid copolymers.
9. The coated steel plate according to claim 1 or 2, wherein, The coating further contains silicon dioxide.
10. A method for manufacturing a coated steel sheet, as described in any one of claims 1 to 9, comprising applying a coating comprising organic resin and wax to at least one side of a base steel sheet and drying it, wherein... The organic resin is selected from at least one of styrene-based resins, epoxy-based resins, phenolic resins, and polyester-based resins. The wax is a polyolefin wax with a melting point of 100℃~145℃ and an average particle size of less than 3.0μm.
11. The method for manufacturing the coated steel plate according to claim 10, wherein, The maximum temperature reached by the base steel plate during drying is above 60°C and below the melting point of the wax.
12. The method for manufacturing the coated steel plate according to claim 10 or 11, wherein, The proportion of total solids in the coating is 1% to 30% by mass.
Citation Information
Patent Citations
Galvanized steel sheet covered with alkali-soluble resin coating film having excellent adhesiveness by adhesive
JP1997170059A
Resin coated metal plate with mold drag resistance and corrosion resistance and its manufacture
JP1998052881A
Alkali-soluble type organic film-coated steel sheet having excellent adhesiveness and anti-mold galling property
JP2000167981A
Coating composition having ability to form lubricative film excellent in press-moldability and scuffing- resistance, and of alkali-soluble type, and metal product having lubricatively treated surface using this composition
JP2000309747A
Steel sheet and method for manufacturing same
CN118056034A